Topical Gel Containing Wrightia tinctoria Extract: Optimization by Central Composite Design, Characterization and Bio-activity Assessment (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The study aimed to develop herbal anti-candida topical gel using ethanolic extract of leaves from the arid zone plant, Wrightia tinctoria, also known as Indrajau. This plant from the Apocynaceae family has been investigated for a wide range of medicinal uses, including pain relief, antifungal effects, inflammation reduction, parasite expulsion, ulcer treatment, dysentery remedy, diabetes management, cancer therapy, fever reduction, and wound healing. These effects are due to the presence of multiple bioactive compounds found in different parts of the plant. This research focused on formulating a pharmaceutically stable herbal gel containing W. tinctoria extract by applying central composite design for optimization and evaluating its phytoconstituents, physical and chemical properties, and various quality control parameters including appearance, pH, spreadability, consistency, homogeneity, viscosity, drug release, stability, skin irritation study, and ex-vivo anti-candida activity in rats. The herbal gel formulation was found to have a pH value of 6.3±0.1, indicating that it is unlikely to cause skin irritation. The prepared herbal gel formulation's spreadability value was discovered to be 22.17±1.5 gm.cm/sec, signifying good spreadability. The extrudability of 89.53%, demonstrated excellent squeezability. During dermal irritation studies, no signs of redness or swelling were observed in the treated animals, indicating the formulation's safety. The major skin irritation index (irritability score) was zero, confirming its suitability for topical application. HPLC analysis confirmed the presence of indirubin, a bis-indole alkaloid, as a major active chemical constituent. The prepared herbal formulation also exhibited acceptable stability as per ICH guidelines. Furthermore, when the gel formulations were applied topically to rats infected with Candida albicans, notable wound healing activities were noted. These tests collectively ensured that the formulated gel was stable, safe, effective, and suitable for use.